The LAUE project: latest developments. Issue 5 (April 2016) - Liccardo, V.; Virgilli, E.; Frontera, F.; Rosati, P.
Abstract: We present the status of the LAUE project devoted to develop a technology for building long focal length Laue lenses for hard X-/soft gamma-ray astronomy (80-600 keV). The Laue lens will be composed of bent crystals of Gallium Arsenide (GaAs, 220) and Germanium (Ge, 111), and, for the first time, the focusing property of bent crystals will be exploited for this field of applications. At the present the goal of the project is the building of a 20 m focal length Laue lens petal capable of focusing X-ray in the energy range 90-300 keV.